The Influence of Customer Satisfaction and Moderation Role of Customer Trust in the Relationship to Customer Loyalty in Digital Banking - Paramadana, Satya; Anthony, Benrik; Az, M. Fariduddin; Simanjuntak, Evi Rinawati (Syntax Literate, 2025)
This research explores how customer trust influences the connection between satisfaction and loyalty, as reflected in share-of-wallet (SOW) and word-of-mouth (WOM) within the context of digital banking. This is done primarily in Indonesia, where digital banking is flourishing, and the study conducted is scarce. A quantitative approach was adopted, utilizing purposive sampling to gather responses from 278 Indonesian digital banking users. The PLS-SEM approach was used to analyze the relationships between key variables through structural equation modeling (SEM). The research revealed that customer satisfaction is significantly affected by factors such as ease of use, service innovation, and the perceived advantages of a product. Additionally, it demonstrated that customer satisfaction significantly affects both the proportion of a customer’s spending and word-of-mouth recommendations. However, contrary to expectations, the study found no evidence that trust moderates the link between satisfaction and share-of-wallet (SAT-SOW) or satisfaction and word-of-mouth (SAT-WOM) within the digital banking sector. This research expands knowledge in the field of digital banking marketing and builds upon prior studies focused on customer-centric service marketing. The study presents a framework that identifies the value associated with SOW and WOM in a modern digital banking service. These findings are beneficial for digital banks, as they can use them to refine their strategies and operations with a customer-centric approach. This, in turn, can help them build lasting, profitable customer relationships and enhance their long-term retention.